WORKING WITH POLYCODE TEXTS WHILE DEVELOPING READING SKILLS IN THE RUSSIAN LANGUAGE - Jurabekova Khabiba Madaminovna (Web of Journals Publishing, 2024)
The author in this article provides an analysis of the concept of polycode text and considers the methodology for using polycode texts in the study of Russian as a foreign language. To develop basic reading skills in Russian as a foreign language, you can choose texts of a narrative nature, informative and descriptive, created using infographics.
Keywords: infographics, skills, polycode text, Russian language, reading.